Mindset, grit, optimism, pessimism and life satisfaction in university students with and without anxiety and/or depression - Tuckwiller, Beth; Dardick, William (Journal of Interdisciplinary Studies in Education, 2018)
We explored mindset, grit, optimism, and pessimism as predictors of university students’ life satisfaction. In consideration of the dual-factor model of mental health, we examined the strength of these predictors on life satisfaction in college students with self-reported anxiety and/or depression and those without. Optimism and pessimism predicted life satisfaction overall, but the relative contribution of each was significantly different based on self-reported anxiety/depression. College students with anxiety and/or depression also demonstrated significantly more fixed mindsets, lower levels of grit, optimism and life satisfaction, and higher levels of pessimism. We discuss the implications of these findings for university wellness programming and initiatives, and future research directions investigating these constructs for university students.